2021
DOI: 10.3329/kyamcj.v12i1.53360
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Impacted Mandibular Third Molar Teeth in Rangpur Region, Bangladesh: A Radiological Evaluation

Abstract: Background: Third molar is the most commonly impacted tooth in the oral cavity and accounts for large of all impactions. The most common complication in the extraction of the third mandibular molars is nerve and vessels damage. Therefore, thorough radiographic assessment is a necessary to avoid these surgical complications. Objective: The purpose of this study was to evaluate the frequency, angulation, depth of the impacted mandibular third molars and its relationship with ramus on radiographs. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(18 reference statements)
0
0
1
Order By: Relevance
“…Winter classified the impacted teeth according to their inclination into mesioangular, horizontal, distoangular, vertical, and inverted. In our study the distoangular pattern was the most common angle in the maxillary arch this finding was inconsistent with Ishwarkumar (2019) [10] Whilst, the mesioangular pattern was the most common angle in the mandibular arch which was consistent with consistent with Prodhan (2021) [13] who was found that the mesioangular pattern of angulation was most prevalent in their studies and inconsistent with Ishwarkumar (2019) [10] who reported that the vertical pattern was high in number also. However, there was a significant correlation between the age group 30 -60 years with both mesioangular patterns in the mandibular arch and distoangular patterns in the maxillary arch.…”
Section: Discussioncontrasting
confidence: 76%
“…Winter classified the impacted teeth according to their inclination into mesioangular, horizontal, distoangular, vertical, and inverted. In our study the distoangular pattern was the most common angle in the maxillary arch this finding was inconsistent with Ishwarkumar (2019) [10] Whilst, the mesioangular pattern was the most common angle in the mandibular arch which was consistent with consistent with Prodhan (2021) [13] who was found that the mesioangular pattern of angulation was most prevalent in their studies and inconsistent with Ishwarkumar (2019) [10] who reported that the vertical pattern was high in number also. However, there was a significant correlation between the age group 30 -60 years with both mesioangular patterns in the mandibular arch and distoangular patterns in the maxillary arch.…”
Section: Discussioncontrasting
confidence: 76%